Progress in structural and functional study of the bacterial phenylacetic acid catabolic pathway, its role in pathogenicity and antibiotic resistance - Jiao, Min; He, Wenbo; Ouyang, Zhenlin; Shi, Qindong; Wen, Yurong (Frontiers in Microbiology, 2022)
Phenylacetic acid (PAA) is a central intermediate metabolite involved in bacterial degradation of aromatic components. The bacterial PAA pathway mainly contains 12 enzymes and a transcriptional regulator, which are involved in biofilm formation and antimicrobial activity. They are present in approximately 16% of the sequenced bacterial genome. In this review, we have summarized the PAA distribution in microbes, recent structural and functional study progress of the enzyme families of the bacterial PAA pathway, and their role in bacterial pathogenicity and antibiotic resistance. The enzymes of the bacterial PAA pathway have shown potential as an antimicrobial drug target for biotechnological applications in metabolic engineering.